Characterization of the effects of cannabinoid receptor deletion on energy metabolism in female C57BL mice - Sotzen, Morgan; Ahmed, Ahmed; Olson, L. Karl; Alshaarawy, Omayma (Frontiers in Endocrinology, 2024)
Background: Despite the evidence that energy balance is regulated differently in females and that the endocannabinoid system is sexually dimorphic, previous studies on the endocannabinoid system and energy balance predominantly used male models.Here, we characterize the effects of cannabinoid receptor deletion on body weight gain and glucose metabolism in female C57BL mice.Methods: Female mice lacking the cannabinoid-1 receptor (CB1R -/-), cannabinoid-2 receptor (CB2R -/-), or both receptors (CB1R -/-/CB2R -/-) and wild-type (WT) mice were fed with a low (LFD; 10% of calories from fat) or high-fat diet (HFD; 45% of calories from fat) for six weeks.Results: Female WT mice fed with HFD gained significantly more weight than WT mice fed with LFD (p < 0.001). Similar pattern was observed for CB1R /-mice fed with HFD compared to CB2R -/-mice fed with LFD (p < 0.001), but not for CB1R -/-fed with HFD vs.LFD (p = 0.22) or CB1R -/-/CB2R -/-fed with HFD vs. LFD (p = 0.96). Comparing the 4 groups on LFD, weight gain of CB1R -/-mice was greater than all other genotypes (p < 0.05). When fed with HFD, the deletion of CB1R alone in females did not attenuate weight gain compared to WT mice (p = 0.72). Female CB1R -/-/CB2R -/-mice gained less weight than WT mice when fed with HFD (p = 0.007) despite similar food intake and locomotor activity, potentially owing to enhanced thermogenesis in the white adipose tissue. No significant difference in weight gain was observed for female CB2R -/-and WT mice on LFD or HFD. Fasting glucose, however, was higher in CB2R -/-mice fed with LFD than all other groups (p < 0.05).The effects of cannabinoid receptor deletion on glucose metabolism in female mice were similar to previously published findings on male mice, yet the effects on body weight gain and thermogenesis were attenuated in CB1R -/-mice.